2022
DOI: 10.1039/d2ce00168c
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure bandgap engineering and amorphization in TiNb2O7 single crystals

Abstract: Titanium niobate (TiNb2O7) possesses excellent photocatalytic, dielectric properties, and lithium-insertion capacity. And high-pressure (HP) is a powerful tool for bandgap engineering aiming at widening their applications. Herein, we report the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Meanwhile, in the decompressed sample (Figure 5d), the arc diffraction pattern imposed on a diffuse halo, further suggesting the amorphous feature of the obtained structure. 26 These findings showed that CuSCN transformed from the crystalline phase to amorphous form, confirming the irreversible amorphization transition, which is in line with the Raman and IR results.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Meanwhile, in the decompressed sample (Figure 5d), the arc diffraction pattern imposed on a diffuse halo, further suggesting the amorphous feature of the obtained structure. 26 These findings showed that CuSCN transformed from the crystalline phase to amorphous form, confirming the irreversible amorphization transition, which is in line with the Raman and IR results.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…In contrast, the modes at 111 and 430 cm –1 are found to shift toward lower wavenumbers with increasing pressure, indicating that the Cu–N/SCN bonds elongate under pressure . This is probably due to the fact that when applying pressure, the bridge SCN bonds are more readily bent, leading to the rotation of the CuNS 3 tetrahedron without damaging its configuration . Namely, when the CuNS 3 tetrahedron was compressed, the Cu–N/SCN bonds were stretched, leading to a transition of CuSCN from the β phase to the α phase.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation